Pharmacokinetic Comparison of Subcutaneous and Intravenous Nadroparin Administration for Thromboprophylaxis in Critically Ill Patients on Vasopressors - Cihlar, Radek; Sramek, Vladimir; Papiez, Adriana; Penka, Miroslav; Suk, Pavel (Pharmacology, 2020)
INTRODUCTION: Critically ill patients are exposed to a high risk of developing thromboembolism. Moreover, standard prophylaxis with subcutaneous (SC) heparin is less efficient in patients requiring vasopressors. The aim is a comparison of pharmacokinetics between SC and intravenous (IV) applied nadroparin. METHODS: Thirty-eight ventilated ICU patients requiring vasopressor support were randomized into a single dose of nadroparin 3,800 IU (0.4 mL) subcutaneously (SC group) or 1,900 IU (0.2 mL) intravenously (IV group). Anti-factor Xa activity (anti-Xa) was observed over 24 h; data are stated as median (IQR). RESULTS: Peak anti-Xa was significantly higher in the IV group 0.42 (0.39-0.43) IU/mL than in the SC group 0.16 (0.09-0.18) IU/mL (p < 0.001). There was a trend towards higher area under the curve (AUC) of anti-Xa in the SC group 1.41 (0.41-1.80) IU/mL × h than in the IV group 1.04 (0.93-1.13) IU/mL × h (p = 0.08). In the SC group, there was a negative correlation between anti-Xa AUC and both capillary refill time Xa (r = -0.86) and norepinephrine dose (r = -0.68). In the IV group, anti-Xa decrease half-life was 1.6 (1.4-2.0) h. CONCLUSIONS: IV administration of 1,900 IU of nadroparin led to a predictable effective peak anti-Xa. After SC administration, anti-Xa was heterogeneous and significantly influenced by peripheral perfusion.
Keywords: Factor Xa; Prophylaxis; žilní tromboembolie; antikoagulancia; Female; Nadroparin; Administration, Intravenous; kritický stav; Anti-factor Xa activity; ženské pohlaví; intravenózní podání; Anticoagulants; Venous Thromboembolism; Low molecular weight heparin; lidé; Pharmacokinetics; injekce subkutánní; Humans; Male; Aged; Vasoconstrictor Agents; Injections, Subcutaneous; Vasopressors; nadroparin; vazokonstriktory; lidé středního věku; senioři; mužské pohlaví; Thromboembolism; Middle Aged; Critical Illness; faktor Xa